Bibliometric analysis of organizational citizenship behavior using scopus database (Lighthouse Publishing, 2023)
Organizational Citizenship Behavior (OCB) is one of the topics that continue to be discussed in organizational studies. This article aims to provide an overview of the intellectual landscape of OCB research by performing bibliometric analysis using VOSviewer. Data is taken from Scopus and includes articles on OCB published from 2019 to 2023. The results of the analysis show that OCB research has grown rapidly over the past three decades, with a significant increase in the number of publications and the number of citations. The article also points out that there are several key themes in OCB research, such as the conceptualization of OCB, factors that influence OCB, as well as the impact of OCB on organizations. However, some gaps in OCB research still need further investigation, such as contextual factors that influence OCB and the relationship of OCB to other topics in organizational studies. A Bibliometric analysis using VOSviewer can provide a clear picture of the intellectual landscape of OCB research and help researchers to identify trends and gaps in OCB research.